2016
DOI: 10.1038/srep19563
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic analysis of severe fever with thrombocytopenia syndrome virus from Zhoushan Islands, China: implication for transmission across the ocean

Abstract: From June 2011 to August 2014, 21 cases of infection by severe fever with thrombocytopenia syndrome bunyavirus (SFTSV) were confirmed in Zhoushan Islands in the Eastern coast of China. To identify the source of SFTSV in Zhoushan Islands, the whole SFTSV genomes were amplified and sequenced from 17 of 21 patients. The L, M, and S genomic segments of these SFTSV strains were phylogenetically analyzed together with those of 188 SFTSV strains available from GenBank. Phylogenetic analysis demonstrated SFTSV could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 28 publications
5
79
0
1
Order By: Relevance
“…Transmission feeding experiments have shown that ticks feeding on SFTSV-infected mice can acquire the virus and that SFTSVinfected ticks can also transmit the virus to mice during feeding (Niu et al, 2013). Phylogenetic studies on SFTSV sequences have revealed that the migration of birds could be a potential source for the spread and geographic expansion of SFTSV (Fu et al, 2016;Shi et al, 2017;Yoshikawa et al, 2015). The results of these studies suggest that the circulation of SFTSV between ticks and animals may be necessary for the maintenance of SFTSV in nature.…”
Section: Introductionmentioning
confidence: 98%
“…Transmission feeding experiments have shown that ticks feeding on SFTSV-infected mice can acquire the virus and that SFTSVinfected ticks can also transmit the virus to mice during feeding (Niu et al, 2013). Phylogenetic studies on SFTSV sequences have revealed that the migration of birds could be a potential source for the spread and geographic expansion of SFTSV (Fu et al, 2016;Shi et al, 2017;Yoshikawa et al, 2015). The results of these studies suggest that the circulation of SFTSV between ticks and animals may be necessary for the maintenance of SFTSV in nature.…”
Section: Introductionmentioning
confidence: 98%
“…Six SFTSV genotypes were classified (A-F) [12]. Both isolates in the present study belonged to genotype B, with high bootstrap values.…”
Section: Case Presentationmentioning
confidence: 53%
“…All sequences, except for the two bases in the two isolates, were identical, and belonged to type B, providing genetic evidence that the SFTSV infection in the present case was likely transmitted by the tick. The difference of the two nucleotides in the M segment, between the tick and patient isolates, could be caused by sequencing errors or replication-induced mutations [12]. The evidence that the tick SFTSV was likely transmitted to The SFTSV phylogenetic tree based on the whole genome, which consists of the L segments of the two isolates obtained from the patient's serum (pink dot) and the tick (blue arrow), and other published sequences obtained from the NCBI database (The GenBank accession number is indicated).…”
Section: Ticks Are the Intermediate Vectors For Sftsv Transmission Smentioning
confidence: 99%
“…First, since the first discovery of SFTSV in China in 2009, doctors and health departments were more and more awared of SFTS, and missed diagnosis or misdiagnosis was reduced[2]. Second, SFTSV might has been spread to more areas through humans, ticks, small mammals, or birds[7, 10]. It result in more people have opportunity to be infected with SFTSV.…”
Section: Discussionmentioning
confidence: 99%